Dari Pengalaman Estetis ke Sikap Estetis dan Etis - Jena, Yeremias (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2014)
Every encounter with a work of art has the potential to give birth to the aesthetic experience. The depth of the experience and its transformative effect is different on each person. However, as an experience, its existence is not in doubt. The problem lies on whether an aesthetic experience is something purely subjective or objective. If the aesthetic experience is objective, to what extent can it be accounted for? Could an aesthetic experience encourage certain ethical action? In this paper the author argues that an aesthetic experience is always moving between the directions of a pendulum, namely, when the artwork appeared to the awareness of the subject and when the experiencing subject narrated the experience. The author wants to defend one of the main positions in aesthetics which says that not only the aesthetic experience encourages a particular moral action, the artwork itself might often stand as a medium of a moral struggle for the betterment of the people.